2015
DOI: 10.3389/fnbeh.2015.00329
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Genes in Adolescent Depression: A Systematic Review

Abstract: Numerous studies have reported on the roles of genetic factors in the development of depression in adolescents and young adults. However, there are few systematic reviews that update our understanding of adolescent depression with the biological findings identifying the roles of gene expression and/or polymorphism(s). This review systematically summarized the findings that clearly identified the contribution of a gene to the risk of depression in adolescents between the ages of 10 and 19 years old and young ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…More interestingly, the first-degree relatives of depressed adolescents who were also suicidal had increased lifetime rates of suicidal behavior, which significantly co-segregated with MDD, providing evidence for the familial aggregation of depression in adolescent-onset MDD. Twin studies also confirmed the association of genetic factors in adolescent depression, although there are very few longitudinal twin studies of adolescent depression ( Rice, 2009 ; Xia and Yao, 2015 ). Although this study was conducted in adolescent females, the only twin study reported to date confirmed that the prevalence of MDD in adolescent co-twins was much higher (up to 36%) in monozygotic twins than in dizygotic twins.…”
Section: Risk Factors For Adolescent Major Depressive Disordermentioning
confidence: 96%
“…More interestingly, the first-degree relatives of depressed adolescents who were also suicidal had increased lifetime rates of suicidal behavior, which significantly co-segregated with MDD, providing evidence for the familial aggregation of depression in adolescent-onset MDD. Twin studies also confirmed the association of genetic factors in adolescent depression, although there are very few longitudinal twin studies of adolescent depression ( Rice, 2009 ; Xia and Yao, 2015 ). Although this study was conducted in adolescent females, the only twin study reported to date confirmed that the prevalence of MDD in adolescent co-twins was much higher (up to 36%) in monozygotic twins than in dizygotic twins.…”
Section: Risk Factors For Adolescent Major Depressive Disordermentioning
confidence: 96%
“…However, in spite of these functional consequences, systematic reviews of the results of association studies suggest that this BDNF genotype does neither exert a major influence on the development of depression (7)(8)(9), nor on the serum BDNF levels (10). However, the influence of the Val66Met BDNF (rs6265) polymorphism may depend on age group, gender, and ethnicity (7,(11)(12)(13)(14). Moreover, according to other meta-analyses interesting results were obtained concerning an association with the results of drug treatment (more specifically in Asian gender and when treated with selective serotonin reuptake inhibitors; SSRIs) (15,16) and vulnerability with life stress (17).…”
Section: Introductionmentioning
confidence: 99%
“…The main target of SSRIs, the serotonin transporter (5-HTT, SERT), broadly influences serotonergic neurotransmission and is encoded by the SLC6A4 gene. In a polymorphic SLC6A4 promoter region, the functional insertion/deletion polymorphism 5-HTTLPR and the functionally related single nucleotide polymorphism rs25531 are discussed as risk factors for the psychopathology of MDD (Xia and Yao, 2015) and frequently associated with robust neural correlates of MDD, like reduced hippocampal volumes (eg, Frodl et al, 2008). Starting with the seminal study of Hariri and colleagues (Hariri et al, 2002), numerous imaging genetic studies also investigated the association of the 5-HTTLPR region and amygdala activity, with several replications (eg, Dannlowski et al, 2010) but, however, also controversially discussed results (cf.…”
Section: Introductionmentioning
confidence: 99%